Psychosocial distress and associated factors among adult cancer patients at oncology: a case of Ethiopia - Baye, Astewle Andargie; Bogale, Sitotaw Kerie; Delie, Abebu Tegenaw; Melak Fekadie, Mengistu; Wondyifraw, Haileyesus Gedamu; Tigabu, Mengistu Ewunetu; Kebede, Mulu (Frontiers in Oncology, 2023)
Background: Psychosocial distress is a chronic burden for cancer survivors, which impacts both their quality of life and their oncologic prognosis. Although the national cancer prevention and control program in Ethiopia has made efforts in cancer prevention, control, and management by implementing the national cancer control plan 2016-2020, no enough evidence about psychosocial distress among adult cancer patients. So it is critical to understand the magnitude of psychosocial distress and the factors that contribute to it.Objective: To assess the prevalence of psychosocial distress and associated factors among adult cancer patients at oncology units in the Amhara regional state, Ethiopia. 2022.A multi-center institution-based cross-sectional study was conducted among a sample of 605 adult cancer patients from April 30-June 22, 2022. A systematic random sampling technique was employed to select the study units. And data were collected through interviewers administered questionnaires by using the validated and pretested tools. Distress was assessed using the Questionnaire on Stress in Cancer Patients Revised 10. Both bivariable and multivariable logistic regression was used to describe the association between dependent and independent variables. Independent variable with p-value less than 0.25 in the bivariable logistic regression analyses were entered into multivariable logistic regression model. Variables with pvalue < 0.05 in the multivariable logistic regression analyses were considered as statistically significant associated factors of psychosocial distress.Result: A total of 593 adult cancer patients took part in this study with mean age of 46.86±14.5 years. The overall prevalence of psychosocial distress was 63.74%. Variables such as being female (AOR=1.98, 95% CI: 1.24-3.17), patients who lives in rural areas (AOR=2.3, 95% CI:1.49-3.54), community based health insurance utilization (AOR=0.34, 95% CI: 0.23-0.51), patients on chemotherapy treatment (AOR=2.72, 95% CI: 1.38-5.39), patients with comorbidity (AOR=3.2, 95% CI: 1.67-6.10), and symptom burdens such as severe fatigue (AOR=1.65, 95% CI:1.09-2.39) and severe nausea (AOR=2.07, 95%CI: 1.43-3.00) were statistically associated with psychosocial distress.In general, the findings of this study showed a relatively high magnitude in which around two-thirds of patients experienced psychosocial distress. It is better to establish and enforce the integration and coordination of psychosocial-oncology service programs at national level with parallel guidelines and policies.